Meta-analysis and systematic review of gout prevalence in the heart/lung transplantation population - Chui, Benedict; Day, Richard; Umashankar, Eshwar; Abdel Shaheed, Christina; Keogh, Anne; Girgis, Laila; Penglase, Ross (Frontiers in Transplantation, 2024)
Introduction: Gout may complicate solid organ transplantation with potentially serious consequences. An accurate prevalence of gout in the heart/lung transplant population is unknown. Objectives: This study aimed to estimate the prevalence of gout in the heart and/or lung transplantation population through a systematic review and meta-analysis. Methods: MEDLINE, Embase, PsycINFO, CENTRAL and Cochrane Library (inception to February 2022) were searched for studies that reported the prevalence and/or incidence of gout in heart and/or lung transplant recipients. Two authors extracted outcomes data. Data were pooled using a random effects model. Overall quality of evidence was assessed using GRADE. Primary outcomes were the prevalence of pre-or post-transplant gout expressed as a prevalence rate (95% CI). Secondary outcomes included risk factors for gout, adverse events, and therapeutic complications of gout treatment. Results: Ten studies were included. Gout prevalence (PR) was 8% pre-transplant (PR = 0.08; 95% CI: 0.05-0.12; 4 studies n=651) and 6% post-transplant (PR = 0.06; 95% CI: 0.06-0.06; 10 studies n=45,298). Post-transplant gout prevalence in heart transplant recipients was almost three times higher than lung transplant recipients (PR=0.16; 95% CI: 0.13-0.20 vs PR=0.06; 95% CI: 0.05-0.06 respectively). Patients with a pre-transplant history of gout had a higher risk of developing post-transplant gout than patients without (RR = 3.61; 95% CI: 2.19-5.95). Factors associated with gout and outcomes for heart and/or lung transplant recipients with gout were comprehensively reviewed from the included studies. Conclusion: Gout is highly prevalent in heart and/or lung transplant patients. Pre-transplant gout is predictive of developing symptomatic post-transplant gout. This has significant implications for management of heart/lung transplant patients.